2017
DOI: 10.1371/journal.pone.0176809
|View full text |Cite|
|
Sign up to set email alerts
|

Gene expression and immunohistochemical analyses of mKast suggest its late pupal and adult-specific functions in the honeybee brain

Abstract: In insect brains, the mushroom bodies (MBs, a higher center) comprise intrinsic neurons, termed Kenyon cells (KCs). We previously showed that the honeybee (Apis mellifera L.) MBs comprise four types of KCs, in addition to the previously known three types of KCs: class I large-type KCs (lKCs), class I small-type KCs (sKCs) and class II KCs, novel class I ‘middle-type’ KCs (mKCs), which are characterized by the preferential expression of a gene, termed mKast. Although mKast was originally discovered during the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 47 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…Although mKast belongs to the α-arrestin family, which is involved in downregulation of membrane receptors (Kaneko et al, 2013 ), the role of mKast in the honeybee is currently obscure. mKast expression in the brain begins at the late pupal stages and is detectable almost exclusively in the adult brain, suggesting its role in regulating adult honeybee behaviors and/or physiology (Yamane et al, 2017 ).…”
Section: Unique Gene/protein Expression Profiles Of Kc Subtypes In Thmentioning
confidence: 99%
“…Although mKast belongs to the α-arrestin family, which is involved in downregulation of membrane receptors (Kaneko et al, 2013 ), the role of mKast in the honeybee is currently obscure. mKast expression in the brain begins at the late pupal stages and is detectable almost exclusively in the adult brain, suggesting its role in regulating adult honeybee behaviors and/or physiology (Yamane et al, 2017 ).…”
Section: Unique Gene/protein Expression Profiles Of Kc Subtypes In Thmentioning
confidence: 99%
“…Four microliters of the protein solution was denatured in sample buffer (50 mM Tris-HCl, pH 6.8, containing 10% glycerol, 2% SDS, 0.002% bromophenol blue, and 3% 2-mercaptethanol), and electrophoresed in polyacrylamide gel (5% for stacking, 10% for separation). Immunoblot analysis was performed essentially as described previously 26 , with some modifications, using 0.2 μg/ml anti-mKast antibody 26 or normal guinea pig IgG (Santa Cruz Biotechnology, Germany) as the first antibody, 0.01 μg/ml goat anti-guinea pig IgG-HRP conjugated (A7289, Sigma, Japan) as the second antibody. Signals were detected using ECL select Western Blotting Detection Reagent (GE Healthcare, Japan) and ImageQuant LAS 4000mini (GE Healthcare, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Here, we conducted gene knockout using CRISPR/Cas9 methods targeting middle-type Kenyon cell-preferential arrestin-related protein ( mKast ), which is preferentially expressed in the mKCs in honeybee MBs 22 . In situ hybridization analysis revealed that mKast is also expressed in optic lobes (OL, a visual center), antennal lobes (AL, an olfactory center), and subesophageal ganglion (SOG, a center for regulating proboscis function) 22 , 26 . In addition, quantitative reverse transcription- polymerase chain reaction (PCR) analysis revealed its adult brain-specific expression 26 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations